DIAGNOSTIC SYSTEM FOR WORKING OUT OF THE STRATEGIES FOR THE DEVELOPMENT OF UNITED LOCAL COMMUNITIES - Vasylchenko , G.V. (The actual problems of regional economy development, 2018)
The article considers the system of diagnostics of the state of a united local community as the basic component of the strategic planning process of development. Diagnostics of community development – objective and subjective (profile, surveys, strategic analysis) is a prerequisite for developing realistic strategies that will have the resource, potential, motives and incentives for implementation. In the article the author uses the practical experience of his own work on development strategies. The materials of the article may be useful to scholars, activists and leaders of local communities who have created or are preparing to create their own united local communities.